Pengaruh Manajemen Konflik dan Budaya Kerja Terhadap Kinerja Organisasi: (Studi pada Pegawai Kantor Penyelenggara Pangandaran) - Ropiul Ropiul; Ading Rahman Sukmara (Jurnal Manajemen Bisnis Digital Terkini, 2024)
This research is motivated by the less than optimal performance of the organization which is marked by the less than optimal achievement of the planned work targets according to the time and proportion that has been set. The less than optimal performance of the organization is thought to be caused by the less effective conflict management and low work culture in the Pangandaran port office. Conflict management managed by the leadership is less effective in controlling the running of the organization which is full of conflicts between employees, both openly and secretly. Employees at the Pangandaran port office seem to form groups that create a gap so that there is no compact cooperation among employees in carrying out their main tasks and work programs. The purpose of this study is to determine how conflict management affects organizational performance, how work culture affects organizational performance, and how conflict management and work culture affect organizational performance. The method used in this study uses a quantitative descriptive method. To analyze it, statistical correlation and multiple regression test data analysis was used using SPSS version 22.00. The results of the study obtained provide the conclusion that conflict management has a positive and significant effect on organizational performance, work culture has a positive and significant effect on organizational performance, and conflict management and work culture have a positive and significant effect on organizational performance.